Organ donation in polish transplantation regulations - Ochotny, Piotr (Studia Ecologiae et Bioethicae, 2019)
The key problem for the modern transplantation practice is the decrease of the number of donors in view of constantly rising demand for tissues and organs. This article is an attempt to respond to the question about whether and to what extent Transplant Act on Cells, Tissues and Organ Retrieval and Transplantation of 1st July 2005 counteracts the decrease of the number of transplants. The author takes the view that Polish transplantation regulations create a favourable environment for organ donation. First of all, article 5 states that transplantation of organs for a therapeutic reason is possible when the deceased person distinctly hadn’t disagreed for such an action. If there are no clear objections against transplantation, and the deceased person does not carry a note of which could suggest otherwise, the physician can legally assume that the person had agreed for an organ sampling (from a presumed consent). Second, Polish law allows organ donation from a living unrelated donors if particular personal reasons justify it. Three, Polish transplantation regulations accept also donation from anonymous donors of bone marrow and other regenerating cells or tissues. Finally, the law admits transplantation of cells, tissues and organs coming from animals to people for healing purposes. That does not actually mean that the existing law is ideal. It must be stressed, however, that the main reason of the decrease of the number of transplants in Poland is the disastrously insufficient state of social consciousness caused by the insufficient public education and lack of educational strategy.